Impact of microplastics on microbial community structure in the Qiantang river: A potential source of N2O emissions - Wang, Zeyu; Liu, Lingxiu; Zhou, Gang; Yu, Hui; Hrynsphan, Dzmitry; Tatsiana, Savitskaya; Robles-Iglesias, Raúl; Chen, Jun (Environmental pollution (1987), 2024)
This study aimed to investigate the spatial distribution of microplastics (MPs) and the features of the bacterial community in the Qiantang River urban river. Surface water samples from the Qiantang River were analyzed for this purpose. The results of the 16S high-throughput sequencing indicated that the microbial community diversity of MPs was significantly lower than in natural water but higher than in natural substrates. The biofilm of MPs was mainly composed of Enterobacteriaceae (28.00%), Bacillaceae (16.25%), and Phormidiaceae (6.75%). The biodiversity on MPs, natural water, and natural substrates varied significantly and was influenced by seasonal factors. In addition, the presence of MPs hindered the denitrification process in the aquatic environment and intensified N2O emission when the nitrate concentration was higher than normal. In particular, polyethylene terephthalate (PET) exhibited a 12% residue of NO3−-N and a 4.2% accumulation of N2O after a duration of 48 h. Further findings on gene abundance and cell viability provided further confirmation that PET had a considerable impact on reducing the expression of nirS (by 0.34-fold) and nosZ (by 0.53-fold), hence impeding the generation of nicotinamide adenine dinucleotide (NADH) (by 0.79-fold). Notably, all MPs demonstrated higher the nirK gene abundances than the nirS gene, which could account for the significant accumulation of N2O. The results suggest that MPs can serve as a novel carrier substrate for microbial communities and as a potential promoter of N2O emission in aquatic environments. [Display omitted] •Microplastics (MPs) exhibited higher community diversity than natural substrates.•The community structure of MPs differed significantly from that of natural water.•Seasonal variations influenced the predominant bacterial species on each substrate.•MPs influenced nitrogen cycle pathways and gene abundance: nirK > nirS.•PET dramatically inhibited denitrification gene expression and NADH production.